Group psychotherapy for female adult survivors of interpersonal psychological trauma: a preliminary study in Scotland. (1st November 2016) - Karatzias, Thanos; Ferguson, Sandra; Gullone, Angela; Cosgrove, Katie
Abstract: Background : There is limited evidence on manualised group interventions that facilitate the development of trauma recovery skills, affect regulation and meaning making for survivors of interpersonal trauma. Aim : The study aimed to provide preliminary evidence on the effectiveness of group psychotherapy (based on Trauma Recovery and Empowerment Model, TREM) for psychological distress in adult survivors of interpersonal trauma. Method : Participants were a consecutive series of female patients ( n = 71) from the waiting lists of five National Health Service (NHS) Boards in Scotland. Participants completed a set of self-rated measures (PCL, CORE, SCL-90, DES and RSES) at baseline, mid-intervention, post-intervention and 3-month follow-up. Results : Effect sizes were small to medium across measures and assessment points at post-treatment and follow-up. With regard to clinical significance, at post-treatment, a proportion of 9.9% to 54.9% of participants achieved clinical significance across measures. At follow-up, a proportion of 9.9% to 62.0% of participants achieved clinical significance across measures. Conclusions : Group psychotherapy may be useful for a proportion of participants and especially so for symptoms of dissociation and self-esteem. Survivors of interpersonal trauma should be offered a choice of individual or group treatment modalities to reduce drop-out rate and maximise outcomes.